IMPROVING STUDENTS’ WRITING SKILL OF NARRATIVE TEXTS BY USING SHORT VIDEOS (A Classroom Action Research at the Eighth Grade Students of SMP Negeri 2 Temanggung in the Academic Year of 2009/2010) - Indrasari, Nunun (Universitas Islam Negeri Raden Intan Lampung, 2015)
This research aims to find out whether short videos can improve students’ writing skill and how far the short videos can improve students’ writing skill at the eighth grade students of SMP Negeri 2 Temanggung. It is also aimed to find out the strengths and weakness of using short videos in the writing class. The approach used in this research is a classroom action research. The action research was conducted in two cycles, in which in the first cycle there were 4 meetings and in the second cycle there were 3 meetings. Every cycle consisted of four steps; planning, implementing, evaluation, and reflection. In collecting the data, the researcher used observation, questionnaires, interviews, field notes, photographs, and tests. The tests were conducted before the action (pre-test) and after the action (post-test). The researcher analyzed the mean score of each test to find out the improvements of students’ writing skill after the action was conducted. The result of the research shows that there are positive improvements in either students’ writing skill or the class situation during the teaching learning process. It can be seen from the result of the test which is improved, from the comparison between the pre-test conducted before the action and the post-test conducted after the action. The mean scores of the test result are 68.22 for the pretest, 75.58 for the post-test in cycle 1, and 78.31 for the post-test in cycle 2. By watching the videos, the students get the stimulus about certain topics so that they can easily construct and generate the ideas into a narrative story based on the video given. They can also arrange better paragraphs based on the generic structure of narrative text. From the t-test computation in the students’ test score, it is showed that the improvement of the students writing skill by using short videos is significant. The t-test computation between the pre-test and the post-test 2 was 8.77. Meanwhile, the t table (tt) for 34 students is 2.04. Since (to)2 is higher than tt, it means that there is a significant difference between the score in the pretest and post-test 2. Some strengths of using short videos in teaching writing which could improve the students’ attitude towards writing in the writing class situation during the teaching learning process were: the students were more motivated in joining the writing class, the videos present the attractive moving pictures and sounds so that they got feeling of relax before they wrote their story, they paid much attention when the videos were played, they were also more confident when they were asked to write individually. However, a weakness of using short videos in writing class was a few students still got difficulties in finding appropriate words with the correct spelling.